In Vitro Shoot-Tip Propagation of Blue Peacock Fern Selaginella willdenowii P.Beauv. (Selaginellaceae) an Ornamental Fern - Nadhirah, Nurul; Maideen, Haja; Zuraida, Ab Rahman; Aliah, Nur; Othman, Ayu Nazreena (Malaysian Applied Biology, 2025)
Selaginella willdenowii, an ornamental fern with iridescent bluish green fronds, is found naturally on forest floors. Many Asian countries consumed it as a traditional medicine and food. It is also suitable for decorative plants since it requires low light and moist conditions, making it perfect for ground covers and house plants. There are currently no efficient methods for propagating this species. Therefore, the goal of this research was to establish an effective in vitro culture propagation method for this species. The shoot-tips were sown in half-strength Murashige & Skoog (MS) as a control, and we observed the most effective culture conditions for shoot-tip proliferation and growth on agar-cultured media at varied concentrations of plant growth regulator (PGR). The findings demonstrated that the culture media supplemented with 0.5 mgL -1 GA3 has a positive effect on the shoot tips, forming a maximum number, lengths of the shoots, and numbers of rhizomes with significant difference (ANOVA, ά<0.05). By using this method, it will be possible to speed up the process for growing a large number of S. willdenowii, and it may also be used to propagate other related plants.